Heat transfer between a fluid and a plate: multidimensional Laplace transformation methods - R. G. Buschman (International Journal of Mathematics and Mathematical Sciences)
Multidimensional Laplace transformations are used to obtain the surface temperature and the surface heat flux of a plate with a fluid flowing across it without solving the complete boundary value problem. It is also shown that the constant initial and boundary values can be relaxed and the method still applies. The solution to the boundary value problem at points away from the surface can be treated similarly